Chamomile (Matricaria chamomilla L.): An overview - Singh, Ompal; Khanam, Zakia; Misra, Neelam; Srivastava, Manoj Kumar (Pharmacognosy Reviews)
Chamomile (Matricaria chamomilla L.) is a well-known medicinal plant species from the Asteraceae family often referred to as the “star among medicinal species.” Nowadays it is a highly favored and much used medicinal plant in folk and traditional medicine. Its multitherapeutic, cosmetic, and nutritional values have been established through years of traditional and scientific use and research. Chamomile has an established domestic (Indian) and international market, which is increasing day by day. The plant available in the market many a times is adulterated and substituted by close relatives of chamomile. This article briefly reviews the medicinal uses along with botany and cultivation techniques. Since chamomile is a rich source of natural products, details on chemical constituents of essential oil and plant parts as well as their pharmacological properties are included. Furthermore, particular emphasis is given to the biochemistry, biotechnology, market demand, and trade of the plant. This is an attempt to compile and document information on different aspects of chamomile and highlight the need for research and development.
Keywords: Amino acid; cadmium; co-cultivation; copper; cultivation; medicinal plant; salicylic acid; secondary metabolites; tissue culture